Collective health research assessment: developing a tool to measure the impact of multistakeholder research initiatives - Anna-Aurora Kork; Carla Antonini; Nicolás García-Torea; Mercedes Luque-Vílchez; Ericka Costa; Juliette Senn; Carlos Larrinaga; Deborah Bertorello; Giampaolo Brichetto; Paola Zaratin; Michele Andreaus (BMC, 2022)
Abstract Background The need to more collaboratively measure the impact of health research and to do so from multidimensional perspectives has been acknowledged. A scorecard was developed as part of the Collective Research Impact Framework (CRIF), to engage stakeholders in the assessment of the impacts of health research and innovations. The purpose of this study was to describe the developmental process of the MULTI-ACT Master Scorecard (MSC) and how it can be used as a workable tool for collectively assessing future responsible research and innovation measures. Methods An extensive review of the health research impact literature and of multistakeholder initiatives resulted in a database of 1556 impact indicators. The MSC was then cocreated by engaging key stakeholders and conducting semi-structured interviews of experts in the field. Results The MSC consists of five accountability dimensions: excellence, efficacy, economic, social and patient-reported outcomes. The tool contains 125 potential indicators, classified into 53 impact measurement aspects that are considered the most relevant topics for multistakeholder research and innovation initiatives when assessing their impact on the basis of their mission and their stakeholders' interests. The scorecard allows the strategic management of multistakeholder research initiatives to demonstrate their impact on people and society. The value of the tool is that it is comprehensive, customizable and easy to use. Conclusions The MSC is an example of how the views of society can be taken into account when research impacts are assessed in a more sustainable and balanced way. The engagement of patients and other stakeholders is an integral part of the CRIF, facilitating collaborative decision-making in the design of policies and research agendas. In policy making, the collective approach allows the evaluation perspective to be extended to the needs of society and towards responsible research and innovation. Multidimensionality makes research and innovations more responsive to systemic challenges, and developing more equitable and sustainable health services.